Investment planning tools for housing stock reconstruction - Zahoretska, Olena (Ways to Improve Construction Efficiency, 2024)
The article presents the conceptual and methodological foundations for evaluating the effectiveness of housing regeneration projects in the context of contemporary urban and socio-economic transformations. The study focuses on the systematization and analysis of investment planning tools that enable evidence-based decision-making regarding the reconstruction of outdated housing stock, ensuring economic viability, technical efficiency, and social justification. The object of the research is the processes of residential stock reconstruction, while the subject is the set of investment design tools, including financial, analytical, techno-economic, spatial, and institutional approaches. The methodology integrates life cycle cost analysis (LCCA), financial modeling (NPV, IRR, DPP), energy modeling, SWOT analysis, GIS technologies, and value engineering. The paper proposes a comprehensive concept for the reconstruction of a deteriorated urban district, incorporating principles of inclusiveness, sustainability, and community engagement. A case study of BIM-based reconstruction of a five-story residential building demonstrates reduced construction time and material waste. A multi-criteria evaluation framework is presented, covering economic, environmental, social, and urban planning indicators. The findings can inform municipal regeneration programs, investment project assessments in development, and policymaking for post-war recovery. The study substantiates the need for a holistic approach that integrates economic feasibility, technical implementability, and social relevance in reconstruction projects. Key investment planning tools are identified to support balanced and sustainable housing modernization decisions.